Proposal for an export-oriented strategy - Pokorný, Zdeněk (2019)
Goal of the diploma thesis was to come up with a proposal of alteration of company POKORNY's Ltd. marketing that would support growth in foreign markets. In order to achieve that, it was neccessary to comprehend and analyze the company's situation, position in the market, business strategy and export strategy. A minor focus was also put on analysis of competitors. Based on the analyses, the thesis identifies shortcomings that inhibits the company's growth. Those related to marketing are further elaborated and specific suggestions for improvements are provided. Result of the thesis should be implementation of the suggestions and growth in the foreign markets.